Life Cycle Carbon Footprint Assessments, Case Study of Malaysian Housing Sector - Gardezi, S.S.S. (Sciendo, 2021)
The ever-increasing concentration of Carbon footprint into the environment has drastically changed the climatic conditions. Among many anthropogenic activities, the housing sector remains one of the major contributors. However, a complete assessment of these environmental impacts throughout the life cycle still remains an area of concern. Most of the study does not assess the impacts by each phase of lifecycle. The current work presents a complete approach for carbon footprint assessment including planning, construction, operational, maintenance and dismantling dispose-off phase. Life Cycle Assessment (LCA) with boundary limitations of 'cradle to grave' was adopted. Thirteen housing units were selected as case study. These included detached, semi-detached and terraced types of construction. Selected units were developed in a virtual environment using Building Information Modeling (BIM). The study observed the average contribution range from 1.48 tons-CO2/yr to 2.85 tons-CO2/yr. On individual basis, the execution phase dominated the five phases with almost 43 . The operational phase shared 39 followed by maintenance (15 ), dismantling dispose-off (1.8 ) and planning at the last (1.5 ). The categorization of environmental impact into embodied and operational carbon footprint observed the embodied part in dominance. A strong positive relationship between the area of housing units and resulting carbon impact was also observed. The work presents one of few environmental studies for a tropical housing sector assessing complete life cycle. The study provides a vital guideline to the designers for ensuring a sustainable environment by assessing and opting less carbon intensive options at early stage of planning and design. Â© 2021 Syed Shujaa Safdar Gardezi et al., published by Sciendo.